2020
DOI: 10.1186/s40561-020-00128-5
|View full text |Cite
|
Sign up to set email alerts
|

A University-industry knowledge transfer online education approach via a cloud-based database global solution

Abstract: Knowledge sharing between different types of organisations, in this case the University-Industry (U-I) relation, contains barriers related to the differentiation of structure and purpose for each organisation. Both the university and industry have to make sure that they have access to data and information. This accessibility enables the value-added process of transforming data into knowledge. The purpose of this paper is the analysis of U-I cooperation-especially under the new online requirementsan illustratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
4
0
3
Order By: Relevance
“…Tzavidas analyzed how knowledge can be shared between universities and industries. Research has shown that the value-added process of transforming data into knowledge is realized by establishing a database with a mutual visit function [15]. Karuoya analyzed the knowledge transfer ability and organizational effectiveness of private universities in Kenya based on the SECI model and determined that strength-ening knowledge socialization can promote the transfer of teacher knowledge to students [16].…”
Section: Hypothesis Proposalmentioning
confidence: 99%
“…Tzavidas analyzed how knowledge can be shared between universities and industries. Research has shown that the value-added process of transforming data into knowledge is realized by establishing a database with a mutual visit function [15]. Karuoya analyzed the knowledge transfer ability and organizational effectiveness of private universities in Kenya based on the SECI model and determined that strength-ening knowledge socialization can promote the transfer of teacher knowledge to students [16].…”
Section: Hypothesis Proposalmentioning
confidence: 99%
“…Universities should be able to maximize this potential to create community resources who have life skills and hard skills, especially in the 4.0 and 5.0 eras like today. learning in higher education should be able to combine academic skills and work skills (Tzavidas, Enevoldsen, & Xydis, 2020). Scouting is an activity that combines learning in the classroom and outside the classroom (learning in the wild).…”
Section: Providing Experiencementioning
confidence: 99%
“…Menurut Stacey ( 2001) dalam (Budihardjo, 2017;Tzavidas et al, 2020) pengetahuan yang dalam kepala seseorang sebagian besar adalah tacit knowledge dan pengekspresiannya dalam bentuk keterampilan profesional. Pengetahuan tacit dapat diartikulasi dan dikonversikan melalui proses yang disebut sebagai sosialisasi.…”
Section: Praktik Transfer Pengetahuan DI Stimlogunclassified
“…Berdasarkan ontologi, pengetahuan dapat berada pada tingkatan individu, kelompok, organisasi, antar organisasi, masyarakat lebih luas. Menurut Parsaye ada tiga pendekatan untuk memperoleh pengetahuan tacit baik dari individu maupun kelompok yaitu wawancara pakar, belajar dari wejangan, dan belajar melalui pengamatan (Tzavidas et al, 2020).…”
Section: Praktik Transfer Pengetahuan DI Stimlogunclassified
See 1 more Smart Citation